ANALISIS PERBANDINGAN HUKUM DALAM SISTEM PEMILIHAN ANGGOTA PERWAKILAN RAKYAT ANTARA DEWAN PERWAKILAN DAERAH REPUBLIK INDONESIA DENGAN RAJYA SABHA REPUBLIK INDIA - Zaenury, Ahmad Goza; Rahmatiar, Yuniar; Abas, Muhamad (Collegium Studiosum Journal, 2023)
General elections are a feature of a democratic country in which implementation is one of the mandates of the constitution and it is the right of every citizen to determine his attitude and support through general elections. The purpose of this research is to see a comparison between the DPD election system in Indonesia and the Rajya Sabha in India which will then become a lesson about the weaknesses and strengths of the two countries. This study uses a normative juridical research method in which the author examines legal materials and supporting documents in conducting research. With the data collection method, namely literature study and document study related to general elections in Indonesia and India. The results of this study indicate that elections in the two countries in terms of regional representation generally have a lot in common where both are regulated in general in the constitutions of the two countries which are then further regulated in derivative laws and regulations. Meanwhile, with regard to the technical aspects, there are several striking differences, including the term between elections and seats and the electoral system used.